Polymer-Based Scaffolds as an Implantable Material in Regenerative Dentistry: A Review - Lubos Lesko; Petra Jungova; Martina Culenova; Andrej Thurzo; Lubos Danisovic (Journal of Functional Biomaterials)
Polymer-based scaffolds have emerged as transformative materials in regenerative dentistry, enabling the restoration and replacement of dental tissues through tissue engineering approaches. These scaffolds, derived from natural and synthetic polymers, mimic the extracellular matrix to promote cellular attachment, proliferation, and differentiation. Natural polymers such as collagen, chitosan, and alginate offer biocompatibility and bioactivity, while synthetic alternatives like polylactic acid (PLA) and polycaprolactone (PCL) provide tunable mechanical properties and degradation rates. Recent advancements highlight the integration of bioactive molecules and nanotechnology to enhance the regenerative potential of these materials. Furthermore, developing hybrid scaffolds combining natural and synthetic polymers addresses biocompatibility and mechanical strength challenges, paving the way for patient-specific treatments. Innovations in 3D bioprinting and stimuli-responsive biomaterials are expected to refine scaffold design further, improving therapeutic precision and clinical outcomes. This review underscores the critical role of polymer-based scaffolds in advancing regenerative dentistry, focusing on their applications, advantages, and limitations.